FEASIBILITY ANALYSIS OF INVESTMENT IN SENTUL MARKET REVITALIZATION YOGYAKARTA - Mei Lutfi Yudhitasari; I Nyoman Dita Pahang Putra (Komunitas Menulis dan Meneliti (Kolibi), 2024)
Revitalization of traditional markets is carried out to increase economic growth. A large enough investment is needed to realize the project, so it is necessary to conduct an investment feasibility analysis. The purpose of this feasibility analysis is to determine the profitability of an investment with the result in the form of a feasible decision or not. This study reviews financial aspects using the parameters of Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (BCR), and Payback Period (PP). Then, the sensitivity of kiosk and los levy rates to NPV and PP values was analyzed. Based on the calculation analysis, the NPV value during the economic period was -8,596,409,255, the IRR was 2.746%, and the BCR was 0.6885. PP analysis shows that the capital issued will not return. Based on the results of the analysis, the revitalization of Sentul Market Yogyakarta is classified as unfeasible from a financial point of view. The sensitivity of kiosk and los levy rates to NPV values shows that revitalization will be feasible if kiosk and los levy rates are increased by at least 68.31%